2019
DOI: 10.1016/j.eats.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Primary Acromioclavicular-Coracoclavicular Reconstruction Using 2 Allografts, TightRope, and Stabilization to the Acromion

Abstract: Acromioclavicular (AC) joint injuries are a common cause of shoulder pain, particularly among young athletes participating in contact sports. Injuries to the AC joint most commonly occur from direct impact at the acromion and are classified as types I to VI. Although most AC joint injuries can be treated nonoperatively, types IV to VI are best treated with surgery, with type III being controversial and most surgeons recommending an initial trial of nonoperative treatment. Although numerous surgical techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…22 High-grade AC separations are usually treated surgically because of instability and pain of the AC joint. 5,8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 High-grade AC separations are usually treated surgically because of instability and pain of the AC joint. 5,8…”
mentioning
confidence: 99%
“…22 High-grade AC separations are usually treated surgically because of instability and pain of the AC joint. 5,8 Several surgical techniques have been proposed to treat AC joint dislocation. 5,7,8,12,18,19,22 In a recent systematic review, the complication rate after use of a suspensory device was 6.2% lower than that after hook plate/K-wire treatment (26.3%), Weaver-Dunn or modified Weaver-Dunn technique (12.8%), or free graft reconstruction (10.3%).…”
mentioning
confidence: 99%
“…In the following years, a multitude of techniques were developed to address this issue, mainly focusing on restoring the integrity of the AC capsule and ligaments. 90,91,97,100 The addition of an AC cerclage to the CC stabilization lead to superior radiological results with a lower incidence of dynamic posterior instability and improved clinical outcomes in a study performed by Hann et al 101 . Furthermore, reconstruction of both the AC and CC ligaments proved to be beneficial in a study conducted by Tauber et al in which a single-bundle technique was compared to a triple-bundle technique using hamstring autografts in 26 patients.…”
Section: Senior Authors Preferred Techniquementioning
confidence: 99%
“…Because of the prevalence of AC joint injuries, there are numerous studies that have described both the nonoperative and operative treatments. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 A systematic review by Beitzel and colleagues 17 looked at 120 studies that collectively describe 162 different techniques for AC management. The study concluded that there is no consensus on a gold-standard procedure.…”
mentioning
confidence: 99%